Acetamide Derivatives of Chromen‐2‐ones as Potent Cholinesterase Inhibitors. Issue 8 (12th July 2017) - Prasad, Suchita; Kumar, Bipul; Kumar, Shiv; Chand, Karam; Kamble, Shashank S.; Gautam, Hemant K.; Sharma, Sunil K.
Abstract : Alzheimer's disease (AD), a neurodegenerative disorder, is a serious medical issue worldwide with drastic social consequences. Inhibition of cholinesterase is one of the rational and effective approaches to retard the symptoms of AD and, hence, consistent efforts are being made to develop efficient anti‐cholinesterase agents. In pursuit of this, a series of 19 acetamide derivatives of chromen‐2‐ones were synthesized and evaluated for their acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory potential. All the synthesized compounds exhibited significant anti‐AChE and anti‐BChE activity, with IC50 values in the range of 0.24–10.19 μM and 0.64–30.08 μM, respectively, using donepezil hydrochloride as the standard. Out of 19 compounds screened, 3 compounds, viz .22, 40, and43, caused 50% inhibition of AChE at 0.24, 0.25, and 0.25 μM, respectively. A kinetic study revealed them to be mixed‐type inhibitors, binding with both the CAS and PAS sites of AChE. The above‐selected compounds were found to be effective inhibitors of AChE‐induced and self‐mediated A β 1–42 aggregation. ADMET predictions demonstrated that these compounds may possess suitable blood–brain barrier (BBB) permeability. Hemolytic assay results revealed that these compounds did not lyse human RBCs up to a thousand times of their IC50 value. MTT assays performed for the shortlisted compounds showed them to be negligibly toxic after 24 h of treatment with the SH‐SY5Y neuroblastoma cells. These results provide insights for further optimization of the scaffolds for designing the next generation of compounds as lead cholinesterase inhibitors. Abstract : From a series of 19 chromen‐2‐one derivatives screened for cholinesterase (AChE/BChE) inhibitition, three compounds (22, 40, and43 ) were found to be potent AChE inhibitors exhibiting mixed‐type inhibition along with effective inhibition of AChE‐induced and self‐mediated A β 1–42 aggregation. The presence of a lipophilic moiety was found to enhance in particular the BChE inhibition activity. These compounds may possess suitable blood–brain barrier permeability.